DISTANCED BY DEFAULT OR THE MANDATES OF MARGINALIZATION IN CAMUS LÉTRANGER - Muratore, Mary Jo (Revista Letras, 2003)
For many readers, Camus LEtranger traces the protagonists evolution from a state of self-indulgent unawareness to one of metaphysical lucidity. This article exposes the shortcomings of such readings by focusing rather on Meursaults fundamentally static nature. In fact, this infamous characters intellectual perspective and situational reality remain virtually unchanged from beginning to end. The sole evolution in evidence is in the vision of others, who fall prey to the prevailing prejudices of a dominant group. In consequence, an unremarkable but well-liked man is transformed into a social pariah via a tidal wave of condemnation while the man himself is unchanged, victimized by conceptual deformations that are imposed upon him. The anti-heros status as an outsider signals, then, not merely the force of public opinion, but the flawed nature of the existentialist endeavor (a movement from which Camus wished ostensibly to be disassociated). The novel comes to represent, not the phenomenon of auto-determined or self-altered identity, but the unstable contingencies imposed from without and from which there is no exit.